2009
DOI: 10.1007/s00421-009-1183-6
|View full text |Cite
|
Sign up to set email alerts
|

Exponential protocols for cardiopulmonary exercise testing on treadmill and cycle ergometer

Abstract: An extended exponential exercise protocol was validated by comparing submaximal and maximal parameters with those obtained by linear protocol. Normal subjects (n = 16, 20-69 years) undertook maximal exercise tests on treadmill and cycle ergometer. The subjects had a wide range of exercise capacity, and all were accommodated by the protocol. Mean oxygen uptake (V(O2)) agreed between protocols at gas exchange anaerobic threshold (theta) (95% CI of difference -0.1 to +0.06 l min(-1)) and at peak (95% CI of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The OMNI-RES scale exhibits a high level of construct validity and has been frequently used during resistance exercise protocols [15].…”
Section: Assessment Of Rate Of Perceived Exertion (Rpe)mentioning
confidence: 99%
“…The OMNI-RES scale exhibits a high level of construct validity and has been frequently used during resistance exercise protocols [15].…”
Section: Assessment Of Rate Of Perceived Exertion (Rpe)mentioning
confidence: 99%
“…and disease have reported that the V O 2 at the anaerobic (AT) or ventilatory (T vent ) threshold is significantly higher when incremental exercise testing is performed on a treadmill than on a cycle ergometer [9,12,15,18,19,23,25,30,32,43]. These Relationship between exercise-induced decreases (Δ) in plasma bicarbonate (HCO 3 -) concentrations and increases in the ventilation above and beyond that needed to support any given increment in oxygen uptake (i.e., excess ventilation) during submaximal and maximal exercise on a cycle ergometer and treadmill.…”
Section: 32b Ventilatory (Anaerobic) Threshold Numerous Studies mentioning
confidence: 99%
“…However, no study has directly investigated the extent to which the exercise modality affects the relationship between GET and HRVT. Considering that HRV varies according to exercise mode (21) and that the physiological strain (measured by peak heart rate and V˙O2 peak) seems to be significantly greater during treadmill exercise than during cycle ergometry (22,23), it is thus reasonable that the level of agreement between the GET and HRVT may also be affected by exercise modality. Another unanswered question is whether the intensity of aerobic exercise can be accurately prescribed using the heart rate response associated with GET and HRVT, by assuming a 1:1 relationship between the %HRR and %V˙O2 R.…”
Section: Introductionmentioning
confidence: 99%